Mistreatment of women during childbirth and its influencing factors in public maternity hospitals in Tehran, Iran: a multi-stakeholder qualitative study - Marjan Mirzania; Elham Shakibazadeh; Meghan A. Bohren; Sedigheh Hantoushzadeh; Farah Babaey; Abdoljavad Khajavi; Abbas Rahimi Foroushani (Reproductive Health, 2023)
Abstract Background Mistreatment during labour and childbirth is a common experience for many women around the world. This study aimed to explore the manifestations of mistreatment and its influencing factors in public maternity hospitals in Tehran. Methods A formative qualitative study was conducted using a phenomenological approach in five public hospitals between October 2021 and May 2022. Sixty in-depth face-to-face interviews were conducted with a purposive sample of women, maternity healthcare providers, and managers. Data were analyzed with content analysis using MAXQDA 18. Results Mistreatment of women during labour and childbirth was manifested in four form: (1) physical abuse (fundal pressure); (2) verbal abuse (judgmental comments, harsh and rude language, and threats of poor outcomes); (3) failure to meet professional standards of care (painful vaginal exams, neglect and abandonment, and refusal to provide pain relief); and (4) poor rapport between women and providers (lack of supportive care and denial of mobility). Four themes were also identified as influencing factors: (1) individual-level factors (e.g., providers’ perception about women’s limited knowledge on childbirth process), (2) healthcare provider-level factors (e.g., provider stress and stressful working conditions); (3) hospital-level factors (e.g., staff shortages); and (4) national health system-level factors (e.g., lack of access to pain management during labour and childbirth). Conclusions Our study showed that women experienced various forms of mistreatment during labour and childbirth. There were also multiple level drivers for mistreatment at individual, healthcare provider, hospital and health system levels. Addressing these factors requires urgent multifaceted interventions.